The sensitivity and specificity of hyperglycosylated hCG (hhCG) levels to reliably diagnose clinical IVF pregnancies at 6 days following embryo transfer - Strom, Charles M. (Springer US, 2012)
OBJECTIVE: To determine the sensitivity and specificity of hyperglycosylated hCG (hhCG) measurements for the diagnosis of clinical pregnancies in the IVF setting and how soon post embryo transfer (ET) a pregnancy can be detected using an ultrasensitive (hhCG) assay. To determine if a single, early hhCG measurement can discriminate between biochemical and clinical pregnancies. DESIGN: A 4 center prospective blinded clinical trial was performed with patients undergoing IVF-ET. Patients had blood drawn and submitted for hhCG analysis on the day of ET and at days 4, 6, 8, and 12 thereafter. First morning urines were collected and submitted for hhCG analysis on days 0, 4, 6, 8, 10 and 12. SETTING: Fertility Centers OUTCOME MEASURES: Clinical pregnancies were defined as an ultrasound study demonstrating a gestational sac and/or heart beat at appropriate gestational ages. RESULTS: Fifty-six of 58 enrolled patients completed the study. There were 25 clinical and 6 biochemical pregnancies. For blastocyst transfers, a single serum or urine hhCG measurement identified pregnancies (both biochemical and clinical) at 6 days post ET with 100% sensitivity and specificity. There were 6 biochemical pregnancies, all following blastocyst transfers. All of these pregnancies were identified by lower values.